White Rot Fungus (Marasmius sp.) Delignification on Sugarcane Bagasse for Bioethanol Production - Darsih, Cici; Wahono, Satriyo Krido; Rosyida, Vita Taufika; Kismurtono, M. (Universitas Muhammadiyah Surakarta, 2015)
Sugarcane bagasse is one of the potential lignocellulose materials for alternative energy especially on the development of bioethanol, the second generation technology. This paper investigates the delignification of sugarcane bagasse by the white rot fungus (Marasmius sp.). Sugarcane bagasse was delignified by fungus; then hydrolyzed by xylane enzyme and fermented by Saccharomyces cerevisiae through simultaneous processes of saccharification and fermentation (SSF). Pretreatment of the sugarcane bagasse was conducted by fungus with various time periods of incubations for 15, 30, and 45 days. SSF of pretreated sugarcane bagasse was conducted for 3, 6, 9, 12, and 15 days. Lignin, cellulose, and hemicellulose were determined by Chesson method. Bagasse structure before and after delignification were determined by Fourier Transform Infrared (FTIR) Spectroscopy. The results showed that the best result of bagasse delignification, containing 16.04% of cellulose, 26.61% of hemicellulose, and 51.89% of cellulose, was on 15 days of incubation. The bioethanol was obtained in 3 days of incubation with bioethanol concentration of 0.85% or 0.4 g/L.